Chimeric protein of internally duplicated α-type carbonic anhydrase from Dunaliella species for improved expression and CO2 sequestration. Issue 9 (September 2016) - Ki, Mi-Ran; Nguyen, Thi Khoa My; Kim, Sung Ho; Kwon, Inchan; Pack, Seung Pil
Graphical abstract: Highlights: The N-terminal 10 residues of Dsp-CA-c were substituted with the first N-terminal 11 residues (NT11) of Dsp-CA-n to make Dsp-nCA-c. NT11 contributed to high soluble expression of host protein Dsp-nCA-c. NT11 contributed to enhanced CO2 hydration activity of Dsp-nCA-c. NT11 contributed to multimerization of Dsp-nCA-c. NT11 conferred remarkable thermostability to Dsp-nCA-c. Abstract: An internally duplicated α-type carbonic anhydrase (CA) from Dunaliella species (Dsp-CA) has been expressed as single-domain derivatives, N- and C- half domains. Although both derivatives have structures similar to that of a known CA (PDB ID:1y7w ), only the C-half domain (Dsp-CA-c) exhibited enzymatic activity, albeit with low solubility. In order to increase the solubility of Dsp-CA-c, its proximal N-terminal amino acids 1–11 were substituted with VSEPHDYNYEK (NT11) of the N-half domain (Dsp-CA-n) which exhibits a high soluble expression yield. The new chimeric gene products, Dsp-nCA-c displayed approximately 2-fold the solubility and activity shown by Dsp-CA-c. Dsp-nCA-c showed increased thermal stability ( ΔT m > 10 °C) by multimerization compared to Dsp-CA-c. Finally, the chimeric protein effectively catalyzed the conversion of CO2 into its calcite form in the presence of CaCl2 . These findings indicate that the substituted NT11 may contribute to soluble expression and enhanced activity of Dsp-nCA-c and cause multimerization which can confer increased thermostability to Dsp-nCA-c. Therefore, N-terminal engineering can be an effective strategy for improving soluble production yield and thermostabillity of CA without disrupting catalytic activity, and the engineered CA could be usefully employed for the development of an efficient enzymatic CO2 sequestration system.